THE TEACHER - MAIN ACTOR IN THE KNOWLEDGE SOCIETY - Vali ILIE; Ecaterina Sarah FRĂSINEANU (Universitaria Publishing House, Craiova, 2020)
We live in a world in continuous transformation, mainly characterized by an informational explosion as well as an aspirational one. This can arouse interest, send to searches and constructions, but it can also create confusion. Therefore, the man needs stable benchmarks. Children and young people need support and guidance. The roles of the teacher are about to be rethought, not so much from the perspective of their change, but from the point of view of adapting to the new demands. The concept of education for the knowledge society starts to be formed in the second half of the 20th century. During this period, the change of the entire educational system of the society is taking place. To effectively promote the development of the knowledge-based economy, it must be understood that information is a factor of production (as well as labor, land and capital). The process of globalization coincides with a fundamental transition to the informational society - a new global information-based community